Pengaruh Pengungkapan ESG Terhadap Nilai Perusahaan Dengan Praktik Good Corporate GovernanceSebagai Variabel Moderasi - Qurniasih, Rismah; Pramurindra, Rezky; Fakhruddin, Iwan; Hinayati, Nur Isna (E-Jurnal Akuntansi, 2024)
In facing global challenges in the business world, Indonesia has made Environmental Social and Governance (ESG) a trend developed to strengthen business strategy. The presence of good corporate governance (GCG) to control management abuse so that the company's value can be increased. This study aims to determine the effect of ESG disclosure on company value with the role of GCG as a moderator. The population of this study were companies indexed by IDX ESG Leader for the period 2020-2023 on the Indonesia Stock Exchange. The use of purposive sampling resulted in 64 companies as research samples. Data analysis was carried out using panel data regression techniques with E-Views 12 software showing that: ESG has a negative effect on company value; institutional ownership and audit committees cannot moderate the effect of ESG on company value. Independent commissioners strengthen the influence of ESG on company value. Keywords: Environmental social and Governance; Good Corporate governance; Company Value.